ANALYTICAL MODEL FOR BUCKLING LENGTH COEFFICIENT DETERMINATION IN STEEL TRUSSES: A LATERAL TORSIONAL BUCKLING APPROACH - Boukhalfa, Dalila; Belaid, Toufik; Slimani, Adel; AMMARI, Fatiha (International Journal for Computational Civil and Structural Engineering, 2024)
This paper presents a contribution to the study of the stability of steel trusses. The paper proposes an analytical model for the determination of the buckling length coefficient of the truss N by the lateral torsional buckling approach. The model is derived by considering the equilibrium of the truss under the action of the applied loads and the buckling load. The buckling load is determined by considering the lateral buckling of the equivalent beam and the interaction between the members. The model is validated by comparing the predicted buckling loads with the experimental results of several steel trusses. The results show that the model can predict the buckling loads with good accuracy. The proposed model is a valuable tool for the design of steel trusses. The model can be used to determine the buckling length coefficient of the truss and to ensure that the truss is safe and reliable. Данная работа представляет собой вклад в исследование устойчивости стальных ферм. Предложена аналитическая модель для определения коэффициента длины смятия N-фермы по методу бокового кручения. Модель построена с учетом равновесия фермы в условиях приложенных нагрузок и нагрузки смятия. Нагрузка смятия определяется с учетом бокового смятия эквивалентной балки и взаимодействия между элементами. Модель проверена путем сравнения прогнозируемых нагрузок на смятие с экспериментальными результатами для нескольких стальных ферм. Результаты показывают, что модель может предсказывать нагрузки на смятие с хорошей точностью. Предложенная модель является ценным инструментом для проектирования стальных ферм. Модель может быть использована для определения коэффициента длины смятия фермы и обеспечения ее безопасности и надежности.